2011
DOI: 10.1007/s11104-011-0977-6
|View full text |Cite
|
Sign up to set email alerts
|

Plant mineral nutrition in ancient landscapes: high plant species diversity on infertile soils is linked to functional diversity for nutritional strategies

Abstract: Ancient landscapes, which have not been glaciated in recent times or disturbed by other major catastrophic events such as volcanic eruptions, are dominated by nutrient-impoverished soils. If these parts of the world have had a relatively stable climate, due to buffering by oceans, their floras tend to be very biodiverse. This review compares the functional ecophysiological plant traits that dominate in old, climatically buffered, infertile landscapes (OCBILS) with those commonly found in young, frequently dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
109
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(121 citation statements)
references
References 148 publications
9
109
0
3
Order By: Relevance
“…In addition, species-rich fynbos vegetation of South Africa (up to 114 species 0.1 ha -1 ) [63] also occurs on ancient, nutrient-impoverished soils. Similarly, some southwestern Australia kwongan shrublands show high local species richness (up to 121 species 0.1 ha -1 ) [64] on heavily leached, infertile sandy soils with extremely low P availability [65].…”
Section: Box 1 Long-term Pedogenesis and Local Plant Species Diversitymentioning
confidence: 99%
“…In addition, species-rich fynbos vegetation of South Africa (up to 114 species 0.1 ha -1 ) [63] also occurs on ancient, nutrient-impoverished soils. Similarly, some southwestern Australia kwongan shrublands show high local species richness (up to 121 species 0.1 ha -1 ) [64] on heavily leached, infertile sandy soils with extremely low P availability [65].…”
Section: Box 1 Long-term Pedogenesis and Local Plant Species Diversitymentioning
confidence: 99%
“…Soils in much of the south west of Western Australia are extremely infertile (e.g. Pate and Beard 1984;Specht and Specht 1999;Lambers et al 2010;Laliberte et al 2014). Although the flora has evolved a wide range of nutrient acquisition strategies to enhance nutrient uptake (e.g.…”
Section: Resilience (Recovery) Of Vegetation (Cover and Height) To Trmentioning
confidence: 99%
“…Malmivaara-Lamsa et al (2008) found that in Finland the tolerance (combining resistance and resilience) of vegetation increased with fertility of the soil. Lambers et al (2010) and Laliberte et al (2014) point out that in the nutrient deficient landscapes of south Western Australia the low availability of plant nutrients constrains plant productivity. Such soil conditions mean that it could take a long time for many plant species to recover from trampling disturbance.…”
Section: Resilience (Recovery) Of Vegetation (Cover and Height) To Trmentioning
confidence: 99%
“…Given that the soil total N is often lower in both very young and very old soils than in middle-aged soils 18,19 and that soil age generally decreases with latitude 14,20 , N concentration in fine roots is expected, in a similar manner to that in leaves 6,9,10 , to increase, peak, and then decrease with increasing latitude. However, some studies have found that the extent of soil N limitation is not associated with latitude 21 , indicating that N concentration in fine roots may not change with latitude.…”
mentioning
confidence: 99%